The lithostratigraphy and history of the Caledonian mélange basin rocks below the Jotun Nappe in Bøverdalen, South Central Norway. - Alsaif, Manar Tawfiq (2015)
The Scandinavian Caledonides have been long studied, yet their ever unfolding complexity renders them far from being fully understood. It has been recognized that the Caledonian Allochthons have neither a linear nor straightforward along-strike relationship. A mélange unit has been recently identified as a separate tectonic unit. This unit is structurally positioned below crystalline nappes previously assigned to the Middle Allochthon. The mélange comprises meta-sediments and minor meta-basalt/gabbro, but most intriguingly, numerous solitary meta-peridotites. These occur as Alpine type meta-peridotites, serpentinites, soapstones and detrital serpentinites. This thesis presents results of a field study of the mélange in the Bøverdalen area structurally below the Jotun nappe, and suggests that this provides evidence that the regional mélange unit was formed in a hyperextended passive margin. The meta-peridotites represent exhumed serpentinized mantle and are intimately associated with meta-sediments. The sediments are garnetiferous chlorite-muscovite schists, graphitic schists, phyllites, amphibolites, meta-sandstones as well as quartzite-pebble dominated conglomerates. It is suggested that this highly heterogeneous mélange unit formed during the early stages of rifting and hyperextension along the Baltican passive margin. Characteristics of the detrital peridotites suggests that serpentinite-talc protrusions may have formed islands. The processes involved are observed in modern margins where the best-studied example is the Iberia-Newfoundland passive margin. Work in present-day margins (mostly seismic reflection data) elucidate the large-scale structure of hyperextended margins, while studies of ancient exposed examples in mountain belts provide insight into the lithology, geochemistry and details of these margins. The widespread distribution of hyperextended margins in modern margins and the increasing number of recognizable ancient margins in mountain-belts indicates the importance of hyperextension during the early stages of the Wilson cycle. Samples collected from the melange unit in the Samnanger area (Bergen) have been dated using U-Pb data from ID-TIMS (isotope-dilution thermal ionization mass spectrometry) analysis of zircon and rutile. These yielded two age groups, ~420 Ma and ~476.23 - 487 Ma, however, both of these bodies are thought to represent intrusive activity post-dating the development of the mélange. Tectonic reconstructions that account for such complexity may not only explain the origin of peridotite bearing mélange units, they may also aid the understanding of the exotic terranes identified in the Scandinavian Caledonides.